+0  
 
-7
255
1
avatar+956 

The solutions to  are... 

 Mar 8, 2019
 #1
avatar+111438 
+2

(x + 3) -  4 / (x - 1) = 5           multiply through by  x - 1

 

(x - 1)(x + 3) - 4  = 5(x - 1)       simplify

 

x^2 + 2x - 3 - 4  =  5x - 5

 

x^2 + 2x - 7  = 5x - 5       add 5, subtract 5x   to/from both sides

 

x^2 - 3x - 2   =  0     using the quadratic formula to find the solutions

 

3 ±√[(-3)^2-  4(1)(-2) ]             3 ±√ [ 9 + 8]            3 ±√17

________________  =  _____________  =     ________   =    x

         2(1)                              2                                2

 

 

cool  cool  cool

 Mar 8, 2019

8 Online Users

avatar